2007
DOI: 10.1093/icesjms/fsm159
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of the Brazilian sharpnose shark (Rhizoprionodon lalandii) from southeastern Brazil

Abstract: Motta, F. S., Namora, R. C., Gadig, O. B. F., and Braga, F. M. S. 2007. Reproductive biology of the Brazilian sharpnose shark (Rhizoprionodon lalandii) from southeastern Brazil. – ICES Journal of Marine Science, 64: 1829–1835. The reproductive biology of the Brazilian sharpnose shark, Rhizoprionodon lalandii, off southeastern Brazil was investigated using data from gillnet landings. The size-at-maturity for males and females was estimated to be 59 and 62 cm total length (LT), respectively. Ovarian fecundity ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
1
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 14 publications
3
32
1
14
Order By: Relevance
“…Interestingly, in the same genus, Motta et al (2007) reported size-at-first maturity of Rhizoprionodon lalandii as 62 cm TL for females, 59 cm TL for males in south-eastern Brazil, which were quite similar to our estimates of the same genus; where as Lessa (1988) reported 56 cm TL for females and 52 cm TL for males for same species in Maranhao (north), Brazil. In this study, the females and males were found to be mature at a larger size, compared to previous studies and it is possible that differences could have resulted from distinctive oceanographic conditions in the region, or fisheries influence, regional differences, or sampling difference which could cause differences in biological parameters between populations, such as maximum size, growth rate, size-at-maturity and fecundity (Parsons, 1993;Lombardi-Carlson et al, 2003;Motta, et al, 2007).…”
Section: Length-weight Relationshipssupporting
confidence: 87%
See 3 more Smart Citations
“…Interestingly, in the same genus, Motta et al (2007) reported size-at-first maturity of Rhizoprionodon lalandii as 62 cm TL for females, 59 cm TL for males in south-eastern Brazil, which were quite similar to our estimates of the same genus; where as Lessa (1988) reported 56 cm TL for females and 52 cm TL for males for same species in Maranhao (north), Brazil. In this study, the females and males were found to be mature at a larger size, compared to previous studies and it is possible that differences could have resulted from distinctive oceanographic conditions in the region, or fisheries influence, regional differences, or sampling difference which could cause differences in biological parameters between populations, such as maximum size, growth rate, size-at-maturity and fecundity (Parsons, 1993;Lombardi-Carlson et al, 2003;Motta, et al, 2007).…”
Section: Length-weight Relationshipssupporting
confidence: 87%
“…In this study, the females and males were found to be mature at a larger size, compared to previous studies and it is possible that differences could have resulted from distinctive oceanographic conditions in the region, or fisheries influence, regional differences, or sampling difference which could cause differences in biological parameters between populations, such as maximum size, growth rate, size-at-maturity and fecundity (Parsons, 1993;Lombardi-Carlson et al, 2003;Motta, et al, 2007). Size at birth estimated in the study was 25-30 cm TL which was larger than those reported (as 21-26 cm TL) earlier by Appukuttan and Nair (1988).…”
Section: Length-weight Relationshipsmentioning
confidence: 45%
See 2 more Smart Citations
“…However, despite generally high fecundity, these small sharks are under some pressure from overfishing in Brazil, where R. lalandii is listed as locally 'Vulnerable' due to intense harvest of all size and age classes in artisanal gillnet fisheries (Rosa et al, 2004;Motta et al, 2005Motta et al, , 2007. Rhizoprionodon lalandii made up 83% of the samples from Guyanese fish markets.…”
Section: Discussionmentioning
confidence: 99%